2005
DOI: 10.1111/j.1439-0434.2005.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplasma Association with Gerbera Phyllody in Australia

Abstract: Gerbera (Gerbera jamesonii L.) plants with phyllody symptoms (green flower) were observed in Central Queensland, Australia. Leaves and flowers from both symptomatic and asymptomatic healthy plants were examined by transmission electron microscopy (TEM). The presence of pleomorphic bodies similar to phytoplasma was observed exclusively in diseased plants. Polymerase chain reaction (PCR) with phytoplasmaspecific primers confirmed the presence of phytoplasma DNA in the infected plants. Further DNA sequencing anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…To date, genetically different phytoplasmas have been identified in diseased ornamentals. However, they are mainly members of the 16SrI group, subgroups B, C and A (Griffiths et al., 1994; Tanne et al., 2000; d'Aquilio et al., 2002; Kaminska et al., 2003; Rojas‐Martinez et al., 2003; Bertaccini et al., 2005; Siddique, 2005). This is in agreement with our data showing that most of the phytoplasmas infecting ornamental plants in Iran are assigned to ‘ Candidatus Phytoplasma asteris’.…”
Section: Resultsmentioning
confidence: 99%
“…To date, genetically different phytoplasmas have been identified in diseased ornamentals. However, they are mainly members of the 16SrI group, subgroups B, C and A (Griffiths et al., 1994; Tanne et al., 2000; d'Aquilio et al., 2002; Kaminska et al., 2003; Rojas‐Martinez et al., 2003; Bertaccini et al., 2005; Siddique, 2005). This is in agreement with our data showing that most of the phytoplasmas infecting ornamental plants in Iran are assigned to ‘ Candidatus Phytoplasma asteris’.…”
Section: Resultsmentioning
confidence: 99%
“…However,Hong et al ( 2005 ) detected and identifi ed phytoplasmas associated with witches' broom disease in Cassia surattensis in China. A new phytoplasma was identifi ed as infecting Cassia italica in Oman(Al-Saady et al 2008 ) Siddique ( 2006 ). reported phyllody on Gerbera jamesonii in Australia, whileRibeiro et al ( 2006 ) reported shoot proliferation in Begonia in Brazil Jones and Arocha ( 2006 ).…”
mentioning
confidence: 99%
“…Gerbera jamesonii : green deformed flowers with many small petals; the infected plants did not die after the infection, but continued to grow new suckers that produced green deformed flowers (Siddique, );…”
Section: Appendix a – Symptoms On Plants Other Than Cydonia Mill Frag...mentioning
confidence: 99%